Effect of Coexistent Hydrogen on the Selective Production of Ethane by Dehydrogenative Methane Coupling through Dielectric-Barrier Discharge under Ordinary Pressure at an Ambient Temperature. (1st January 2014) - Konno, Katsuya; Onoe, Kaoru; Takiguchi, Yasuyuki; Yamaguchi, Tatsuaki
Abstract : The effect of coexistence of hydrogen on the product selectivity to ethane from methane by dielectric-barrier discharge (DBD) reactor was examined experimentally under ordinary pressure without use of catalyst and external heating. By the dilution of methane with hydrogen, both the increase of methane conversion and the decrease of alkene production were observed, improving the selectivities to ethane by ca . 70%.